Development of Internet-Based System on the Implementation of The Student Satisfaction Survey Against Lecturer in Semarang Health Polytechnic - Teguh Wahyudi; Warijan Warijan; Suhardono Suhardono (Jurnal LINK, 2013)
Background- As an institution that has been certified by ISO 9001:2008, at the end of each semester, Responsible for Academic Administration to the Study Program/Department of Semarang Health polytechnic need to conduct surveys of students satisfaction to lecturers. Currently, the surveys are carried out with reference to the process ”paper based” so that the management takes time and requires a fee for copying questionnaire. The purpose of research- This study aims to develop an effective and efficient internet-based system administration on the implementation of student satisfaction surveys to the lecturers in terms of both energy and costs. Research Methods- This research is a quasi experiment with cross-sectional research design involving 10 Responsible for Academic Administration and 90 students in each Department/Study Program in the Semarang Health Polytechnic. Data was collected using a set of questionnaires. Results- The data analysis shows 70% of Responsible for Academic Administration said that internet-based system administration is ”effective” to conduct the implementation of student satisfaction surveys to the lecturers. Moreover, 62.2% of student respondents have a perception "good" on the implementation of the online survey system. Suggestion- It is suggested that the researcher need to explain the effectiveness and efficiency of online survey to all of Heads of Department/Program Study Chairs, it is important for the Heads of Department/Study Program Chairs and Director to support on the implementation of student satisfaction surveys to the lecturers, responsible for Academic Administration should avail the facility of online survey to enhance the effectiveness of time and cost efficiency in the implementation of student satisfaction surveys to the lecturers and it is important to do other researches on the effectiveness of online survey in Semarang Health Politechnic in an effort to optimize resources and improve performance to the organization